Immunophenotypic Profile of CD34+ Subpopulations and Their Role in the Diagnosis and Prognosis of Patients with De‐Novo, Particularly Low‐Grade Myelodysplastic Syndromes. Issue 1 (17th October 2018) - Gardikas, Nikolaos; Vikentiou, Myrofora; Konsta, Evgenia; Kontos, Christos K.; Papageorgiou, Sotirios G.; Spathis, Aris; Bazani, Efthimia; Bouchla, Anthi; Kapsimali, Violetta; Psarra, Katherina; Foukas, Periklis; Dimitriadis, George; et al.
Abstract : Background: Myelodysplastic syndromes (MDS) are clonal hematopoietic stem cell disorders with unknown aetiology. Multiparameter flow cytometry (MFC) is being evaluated for the diagnosis and prognosis of MDS. Methods: In the present study, five‐color MFC was performed on bone marrow aspirates of 50 untreated patients, newly diagnosed with MDS and 27 age matched control samples. Patients were classified according to World Health Organization 2016, International Prognostic Scoring System (IPSS), and Revised IPSS (IPSS‐R). Results: Significantly higher CD133+/CD90‐CD45weak, CD117+/TdT‐CD45weak, and CD33+/MPO‐neutrophil precursor percentages on CD34+ cells, as well as a significant decrease of lymphoid and erythroid precursors were observed in the group of MDS patients in comparison to controls. A new scoring system was based on these findings, which can be helpful in discriminating lower risk MDS patients, including those with normal karyotype (a subgroup of MDS with diagnostic challenges). In addition, an increased level of apoptosis of CD34+/CD117+ cells was identified as an independent favorable prognostic factor both for the risk of transformation to acute myeloid leukemia and for overall survival. Conclusions: A new scoring system based on the expression of immature cell antigens on CD34+ cells (by itself or in combination with the Ogata score) can discriminate lower risk MDS patients, including those with normal karyotype, from the normal control group. © 2018 International Clinical Cytometry Society